Body mass index and risk of autoimmune diseases: a study within the Danish National Birth Cohort - Harpsøe, Maria C; Basit, Saima; Andersson, Mikael; Nielsen, Nete M; Frisch, Morten; Wohlfahrt, Jan; Nohr, Ellen A; Linneberg, Allan; Jess, Tine (International journal of epidemiology, 2014)
A possible aetiological link between obesity and certain autoimmune diseases (ADs) has been suggested. We investigated the associations between body mass index (BMI, kg/m2) and 43 ADs. 75,008 women participating in the Danish National Birth Cohort were followed during a median time of 11 years. Diagnoses on ADs were retrieved from the Danish National Patient Register. Cox proportional hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated adjusting for potential confounders (smoking, alcohol, parity and socio-occupational status). During follow-up, 2430 women (3.2%) developed a total of 2607 new-onset ADs. Risk of any autoimmune disease was increased in obese women (HR, 1.27; 95% CI, 1.11 to 1.46) compared with normal weight women (18.5-≤25 kg/m2). Obese women (BMI≥30 kg/m2) were at increased risk of sarcoidosis (HR 3.59; 95% CI, 2.31 to 5.57) and type 1 diabetes mellitus (HR 2.67; 95% CI, 1.71 to 4.17). Risk of dermatitis herpetiformis increased by 14% (95% CI, 1% to 30%) per BMI unit. Conversely, risk of celiac disease and Raynaud's phenomenon decreased by 7% (95% CI, 1% to 13%) and 12% (95% CI, 4% to 19%) per BMI unit, respectively. Further associations between BMI and risk of psoriasis, rheumatoid arthritis and Crohn's disease were suggested. BMI was found to be associated with several Ads. This was most pronounced between obesity and risk of sarcoidosis and and risk of type 1 diabetes mellitus. These novel findings need confirmation and the possible role of adipose tissue-derived immunological changes in the development of autoimmune reactions needs consideration.